Intraportal Islet Autotransplantation Independently Improves Quality of Life After Total Pancreatectomy in Patients With Chronic Refractory Pancreatitis. Issue 3 (28th September 2022) - Chinnakotla, Srinath; Beilman, Gregory J.; Vock, David; Freeman, Martin L.; Kirchner, Varvara; Dunn, Ty B.; Pruett, Timothy L.; Amateau, Stuart K.; Trikudanathan, Guru; Schwarzenberg, Sarah J.; Downs, Elissa; Armfield, Matthew; et al.
Abstract : Objective: To determine if islet autotransplantation (IAT) independently improves the quality of life (QoL) in patients after total pancreatectomy and islet autotransplantation (TP-IAT). Background: TP-IAT is increasingly being used for intractable chronic pancreatitis. However, the impact of IAT on long-term islet function and QoL is unclear. Methods: TP-IAT patients at our center >1 year after TP-IAT with ≥1 Short Form-36 QoL measure were included. Patients were classified as insulin-independent or insulin-dependent, and as having islet graft function or failure by C-peptide. The associations of insulin use and islet graft function with QoL measures were analyzed by using a linear mixed model, accounting for time since transplant and within-person correlation. Results: Among 817 islet autograft recipients, 564 patients [median (interquartile range) age: 34 (20, 45) years, 71% female] and 2161 total QoL surveys were included. QoL data were available for >5 years after TP-IAT for 42.7% and for >10 years for 17.3%. Insulin-independent patients exhibited higher QoL in 7 of 8 subscale domains and for Physical Component Summary and Mental Component Summary scores ( P <0.05 for all). Physical Component Summary was 2.91 (SE=0.57) higher in insulin-independent patients ( P <0.001). No differences in QoL were observed between those with and without graft function, but islet graft failure was rare (15% of patients). However, glycosylated hemoglobin was much higher with islet graft failure. Conclusions: QoL is significantly improved when insulin independence is present, and glycosylated hemoglobin is lower with a functioning islet graft. These data support offering IAT, rather than just performing total pancreatectomy and treating with exogenous insulin.